The Revitalization of Islamic Parenting Values in Hadih Maja Aceh - Putri Rahmawati (At-Tarbiyat, 2021)
Hadih Maja (The Acehnese Proverbs) is oral literature as a wise expression of ancestral’s heritage about the values and philosophies of Acehnese life which is expressed briefly, densely, and with a touch of poetic language. Hadih Maja contains various values and philosophical dimensions so that it becomes a guide in carrying out the daily life of people in Aceh. Most of the Hadih Maja is a crystallization of Islamic values in the cultural system of the Acehnese people. One of the values contained in Hadih Maja is the value of Islamic parenting. This study aimed to describe and interpret some basic principles in the study of concepts Islamic parenting based on Hadih Maja (The Acehnese Proverbs). This research use qualitative method with content analysis techniques. The data collection technique was carried out by studying documents using primary data sources in the form of Hadih Maja collections written by Hasyim MK (1977) and interviews with the community regarding the use of Hadih Maja (The Acehnese Proverbs). The results of this research showed that the Islamic parenting values contained in Hadih Maja were divided into five basic principles. Hadih Maja contains five basic principles of Islamic parenting which are contained in the 20 Hadih Maja Aceh. The five basic principles of Islamic parenting contained in Hadih Maja are: 1) Qudwah Hasanah (Integrated Role Model); 2) Al-'Aadah (Habituation); 3) Al-Mauidzah (Effective Advice); 4) Al-Mulahadzah (Fairness in Care and Control); 5) Al-Ujurah wa al-'Uqubah (Proportional Consequencess). It is concluded that Hadih Maja a cultural product that is valuable and meaningful so to protect this ancestral heritage, this Hadih Maja must have to revitalize so that this valuable cultural treasure will be preserved and will not disappear over time.